Paediatric Palliative Care - describing patient needs and the experiences of caregivers and health care workers in a Cape Town Paediatric Intermediate Care Facility - Daniels, Alexandra Jacqueline (Department of Medicine, 2023)
Introduction: Palliative care has the potential to improve the quality of life for children living with LL or LTC's and their families. However, in the South African context, little is known about the specific care needs of these children and the experiences of caregivers and health care workers during the child's stay at an intermediate / step down facility. Aim: The study describes the population (and care needs) of children admitted to the facility, the experiences of their primary caregivers and the health care workers caring for them. Methodology: This was a descriptive study that utilised elements of both prospective and cross-sectional design. The health records of 25 patients were reviewed and matched caregivers partook in a three-part questionnaire. Focus group discussions were conducted with 15 health care workers at a single point during the study. Results: The majority (48%) of patients were referred to the facility for transitional care, the average length of stay was calculated at 97 days and pain was identified as the most prevalent symptom. Despite significant degrees of worry, most primary caregivers derived emotional strength and spiritual meaning from the experience of caring for their child. Health care workers valued access to training, appropriate resources and support to meet the challenge of caring for children and families with specific care needs. Conclusion/Recommendations: These results conclude that children living with LL or LTC's and their families have complex holistic care needs that require a comprehensive approach. In order to best meet these needs, at ICF level, health care workers need to be assured access to a range of skills, resources and support.